Utilization of Waste Materials for Microbial Carrier in Wastewater Treatment. (20th July 2016) - Le, H. T.; Jantarat, N.; Khanitchaidecha, W.; Ratananikom, K.; Nakaruk, A.
Abstract : This research focused on the ammonium-nitrogen (NH4 -N) removal from the domestic wastewater using the attached growth reactors. Two types of waste material of corncob (biodegradable material) and concrete (nonbiodegradable material) were used as the carrier for microorganisms' attachment. During operation, both reactors achieved absolutely high performance of ammonium removal (up to 99%) and total nitrogen removal (up to 95%). The significant advantage of corncob carrier was that the corncob was able to be a source of carbon for biological denitrification, leading to no external carbon requirement for operating the system. However, the corncob caused an increasing turbidity of the effluent. On the other hand, the concrete carrier required the minimal external carbon of 3.5 C/N ratio to reach the good performance. Moreover, a longer period for microorganisms' adaptation was found in the concrete carrier rather than the corncob carrier. Further, the same physiological and biochemical characteristics of active bacteria were found at the two carriers, which were negative gram, cocci shape, and smooth and white-turbid colony. Due to the effluent quality, the concrete was more appropriate carrier than the corncob for wastewater treatment.